Research and analysis in sport economics and management - Fernández-Gavira, Jesús; Gálvez Ruiz, Pablo; García-Fernández, Jerónimo; García-Villar, Jaume (Revista de Psicología del Deporte, 2017)
This is an introductory article to the present supplement where it is presented a total of 23 research papers, which has been discussed within the VII Iberoamerican Congress of Economics and Management of Sport, where it will be see the standards of quality and scientific rigor usual in these disciplines, which will contribute to a greater and better understanding of the economic dimension of sport in its different perspectives. In this way, it is important to emphasize the integrative nature of the selected works, which reinforce the interdisciplinary and integrating perspective research on issues relating to sport and physical activity. The research areas are as follows, sports psychology, sports economics, sports management and sports marketing institutions among others.
Investigación y análisis de la gestión y economía del deporte
Se trata de un artículo de introducción al presente suplemento, en él se presenta un total de 23 trabajos de investigación, los cuales se han tratado en el VII Congreso Iberoamericano de Economía y Gestión del Deporte, en ellos se pueden observar los estándares de calidad y rigor científico habituales en estas disciplinas, con ello esperamos contribuir a una mayor y mejor comprensión de las diferentes perspectivas de la dimensión económica del deporte. De esta manera, es importante hacer hincapié en la naturaleza integradora de las obras seleccionadas, las cuales refuerzan la perspectiva de la investigación en temas relacionados con el deporte y la actividad física. Las áreas de investigación son las siguientes, psicología del deporte, economía del deporte, gestión del deporte y marketing del deporte entre otros.
Keywords: sports psychology; sports economics; sports management; sports marketing; JCR; Scopus